2019
DOI: 10.1002/jor.24182
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of tendon regeneration with adipose‐derived stem cell

Abstract: The use of Adipose‐Derived Stem Cells (ADSC) has been presented as a new alternative for tendon reconstruction. Have been admitted that ADSCs are related to better outcomes when used in tendon healing. This research was designed to apply the potential of ADSCs in tendon healing. Flexor digitorum superficialis tendon lesion was performed on both legs of eleven New Zealand rabbits and them, at the same time, treated as follows: Suture alone (Group III − Suture, n:10), suture associated with ADSC (Group IV − Sutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
7
0
6
Order By: Relevance
“…Indeed, they are able to differentiate not only into cells of mesodermal origin such as adipocytes [ 1 , 2 ], chondrocytes [ 3 ] and osteocytes [ 4 ], but also into cells of different lineages [ 5 ]. For this reason, they have been extensively investigated for potential therapeutic applications in a variety of pathologies, being also capable of releasing immunosuppressive cytokines such as interleukin-10 (IL-10), or factors promoting tissue regeneration (hepatocyte growth factor, and transforming growth factor-β; TGF-β) [ 6 , 7 , 8 , 9 ]. Stem-cell-based therapies are currently explored for the treatment of ocular diseases [ 10 , 11 , 12 , 13 ], including diabetic retinopathy (DR), in which a vascular complication leads to the disruption of the blood retinal barrier (BRB) [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they are able to differentiate not only into cells of mesodermal origin such as adipocytes [ 1 , 2 ], chondrocytes [ 3 ] and osteocytes [ 4 ], but also into cells of different lineages [ 5 ]. For this reason, they have been extensively investigated for potential therapeutic applications in a variety of pathologies, being also capable of releasing immunosuppressive cytokines such as interleukin-10 (IL-10), or factors promoting tissue regeneration (hepatocyte growth factor, and transforming growth factor-β; TGF-β) [ 6 , 7 , 8 , 9 ]. Stem-cell-based therapies are currently explored for the treatment of ocular diseases [ 10 , 11 , 12 , 13 ], including diabetic retinopathy (DR), in which a vascular complication leads to the disruption of the blood retinal barrier (BRB) [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Спустя 4 недели выявлено, что сухожилия имеют большую площадь сечения, меньшую жёсткость и меньшую предельную растягивающую нагрузку в сравнении с животными, которым МСК не вводили. В данном эксперименте пришли к выводу, что МСК успешно участвуют в дифференцировке теноцитов на ранних стадиях регенерации и вносят значительный вклад в дальнейшую реконструкцию сухожилий [8]. Однако увеличение площади поперечного сечения может ухудшить движение сухожилия впоследствии, а также в данном эксперименте не проведены гистологическая или функциональная оценки, что подразумевает дальнейшие исследования.…”
Section: применение мск для восстановления сухожилий в экспериментеunclassified
“…Таким образом, тканевая инженерия, основанная на репаративном потенциале мезенхимальных стволовых клеток, доставляемых к месту повреждения сухожилия самостоятельно или в сочетании с биосовместимыми конструкциями или гелями, в зависимости от типа повреждения и стадии заболевания является наиболее перспективным направлением регенеративной медицины [8,63,64]. Однако отсутствие протоколов, а также неблагоприятные результаты некоторых исследований предполагают дальнейшее изучение применения мезенхимальных стволовых клеток в регенерации повреждённых сухожилий.…”
Section: заключениеunclassified
See 1 more Smart Citation
“…To determine if ASCs can augment tendon healing, de Lima Santos et al delivered ASCs with suture repair of a rabbit flexor tendon injury. This study showed that ASC delivery significantly improved biomechanical properties of tendon repair as compared with acellular groups.…”
mentioning
confidence: 99%